(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Drug use is a problem for today’s youth. Several factors contribute to this, including biological, psychological, and social development. One way to address this is by improving adolescents’ cognitive skills through the Think-Pair-Share model. In this health program, the team combined TPS with BLS practices. The sample for this activity was 30 students from SMA N 3 Samarinda. The results showed an increase in their knowledge, attitudes, actions, skills, and values related to substance use with a p-value <0.05, and then re-practicing emergency techniques. Furthermore, respondents felt comfortable discussing and enjoyed this health promotion model. Health promotion employs innovative strategies to foster critical thinking, boost confidence, and promote active listening, making it more engaging for today’s youth. Furthermore, the Think-Pair-Share model, combined with training, can be used to optimize the acquisition of new knowledge. In addition, various learning models are needed to make health information enjoyable, especially for adolescents.